1998
DOI: 10.1073/pnas.95.1.364
|View full text |Cite
|
Sign up to set email alerts
|

The cyanobacterium Synechococcus resists UV-B by exchanging photosystem II reaction-center D1 proteins

Abstract: Current ambient UV-B levels can significantly depress productivity in aquatic habitats, largely because UV-B inhibits several steps of photosynthesis, including the photooxidation of water catalyzed by photosystem II. We show that upon UV-B exposure the cyanobacterium Synechococcus sp. PCC 7942 rapidly changes the expression of a family of three psbA genes encoding photosystem II D1 proteins. In wild-type cells the psbAI gene is expressed constitutively, but strong accumulations of psbAII and psbAIII transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
121
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 53 publications
13
121
0
Order By: Relevance
“…The appearance of the D1:2 copy might have contributed to the elimination of the flv4-2 operon relatively early during evolution (Table II). The D1 protein from algae and plants, which is encoded by a single psbA gene, shares more common residues with the D1:2 cyanobacterial D1 copy, including the 130E residue (Svensson et al, 1991;Winhauer et al, 1991;Campbell et al, 1998b;Takishita and Uchida, 1999). These observations suggest that the Q130E D1 form was a successful strategy for the photosynthetic organisms, becoming ubiquitous among them.…”
Section: Evolutionary Trends In Psii Photoprotective Mechanisms In Cymentioning
confidence: 73%
“…The appearance of the D1:2 copy might have contributed to the elimination of the flv4-2 operon relatively early during evolution (Table II). The D1 protein from algae and plants, which is encoded by a single psbA gene, shares more common residues with the D1:2 cyanobacterial D1 copy, including the 130E residue (Svensson et al, 1991;Winhauer et al, 1991;Campbell et al, 1998b;Takishita and Uchida, 1999). These observations suggest that the Q130E D1 form was a successful strategy for the photosynthetic organisms, becoming ubiquitous among them.…”
Section: Evolutionary Trends In Psii Photoprotective Mechanisms In Cymentioning
confidence: 73%
“…However, this is not clearly supported by the radiative stress indicators measured. In addition, repair is thought to be more efficient at elevated temperatures like those encountered in our study (Campbell et al, 1998;van de Poll and Buma, 2009). The fact that surface inhibition was only moderate and that highest PPp occurred in the middle bottle suggests that the photosynthetic machinery of phytoplankton was well adapted to a stratified system and thus not geared to take advantage of fast changes in spectral irradiance.…”
Section: Phytoplankton Photosynthetic Performance and Photoacclimationmentioning
confidence: 81%
“…and Synechococcus sp. In both species, it was found that exposure to moderate doses of UVB results in an increased turnover rate of the D 1 and D 2 reaction centre subunits of PS II, thus, rapidly replacing damaged protein by newly synthesised polypeptides (Campbell et al 1998;Má té et al 1998). The latter authors found that UVB induces the transcription of psbA genes, which encode the D 1 reaction centre protein of PS II.…”
Section: Acclimation Of Photosynthesis To Uv Radiationmentioning
confidence: 81%